A Longitudinal Investigation of Willingness to Pay for Health Insurance in Germany. (20th June 2016) - Bock, Jens‐Oliver; Hajek, André; Brenner, Hermann; Saum, Kai‐Uwe; Matschinger, Herbert; Haefeli, Walter Emil; Schöttker, Ben; Quinzler, Renate; Heider, Dirk; König, Hans‐Helmut
Abstract : Objective: To investigate factors affecting willingness to pay (WTP) for health insurance of older adults in a longitudinal setting in Germany. Data Sources: Survey data from a cohort study in Saarland, Germany, from 2008–2010 and 2011–2014 ( n 1  = 3, 124; n 2  = 2, 761) were used. Study Design: Panel data were taken at two points from an observational, prospective cohort study. Data Collection: WTP estimates were derived using a contingent valuation method with a payment card. Participants provided data on sociodemographics, lifestyle factors, morbidity, and health care utilization. Principal Findings: Fixed effects regression models showed higher individual health care costs to increase WTP, which in particular could be found for members of private health insurance. Changes in income and morbidity did not affect WTP among members of social health insurance, whereas these predictors affected WTP among members of private health insurance. Conclusions: The fact that individual health care costs affected WTP positively might indicate that demanding (expensive) health care services raises the awareness of the benefits of health insurance. Thus, measures to increase WTP in old age should target at improving transparency of the value of health insurances at the moment when individual health care utilization and corresponding costs are still relatively low.